2020
DOI: 10.1371/journal.pone.0232883
|View full text |Cite
|
Sign up to set email alerts
|

Trends and determinants of ever having tested for HIV among youth and adults in South Africa from 2005–2017: Results from four repeated cross-sectional nationally representative household-based HIV prevalence, incidence, and behaviour surveys

Abstract: Background HIV testing contributes to the prevention and control of the HIV epidemic in the general population. South Africa has made strides to improve HIV testing towards reaching the first of the UNAIDS 90-90-90 targets by 2020. However, to date no nationally representative analysis has examined temporal trends and factors associated with HIV testing among youth and adults in the country. Aim This study aimed to examine the trends and associations with ever having tested for HIV among youth and adults aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 19 publications
(22 reference statements)
5
13
1
Order By: Relevance
“…The AGYW who lived with a man were more likely to test for HIV and this could be due to their possibly high sexual activities, hence they are at higher risk of HIV and other sexually transmitted diseases, for which they would visit the healthcare facilities and would also be allowed to test for HIV [ 20 ]. Other studies have found similar results, for example in South Africa by Jooste et al 2020 [ 21 ] and in Tanzania by Mahande et al 2019 [ 22 ].…”
Section: Discussionsupporting
confidence: 68%
“…The AGYW who lived with a man were more likely to test for HIV and this could be due to their possibly high sexual activities, hence they are at higher risk of HIV and other sexually transmitted diseases, for which they would visit the healthcare facilities and would also be allowed to test for HIV [ 20 ]. Other studies have found similar results, for example in South Africa by Jooste et al 2020 [ 21 ] and in Tanzania by Mahande et al 2019 [ 22 ].…”
Section: Discussionsupporting
confidence: 68%
“…The improvement in HIV testing we observed from 2004 is likely explained by the expansion of the HIV testing programme in South Africa, with more people gaining access to HIV testing services. According to a national, representative survey, the percentage of women ever tested for HIV increased from 33% in 2005 to 79% in 2017 [ 31 ]. In the context of CC, a case–control study demonstrated that approximately 10% of women diagnosed with CC were unaware of their HIV positive status [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Assumptions about HIV testing rates are set by calibrating the model to data on the total numbers of tests in adults, proportions of test results that are positive, and proportions of adults who report having ever tested for HIV. 17,22 Rates of ART initiation after diagnosis are assumed to depend on CD4 count, sex and year, with the rates of ART initiation set so that the model matches separately estimated annual numbers of men and women starting ART. 17 The infectivity of treated individuals, per unprotected sex act, is assumed to reduce by a proportion that depends on their baseline CD4 count at ART initiation and their level of viral suppression (see Supplemental Materials, http://links.lww.com/QAI/B811).…”
Section: Methodsmentioning
confidence: 99%